La investigación educativa interdisciplinaria integrada en el Centro de Investigación y Docencia en Educación (CIDE): un aporte de las Unidades Académicas y del INEINA - Alfaro Rodríguez, Magdalena (2010)
The project called Perfiles, Dinámicas y Desafíos de la Educación Costarricense (Profiles, Dynamics and Challenges of the Costa Rican Education) in its various working phases it conducts interdisciplinary educational research at an integrated level at the Centro de Investigación y Docencia en Educación (CIDE) (Research and Teaching Center) from Universidad Nacional in Costa Rica. This article discusses the importance of taking into account outcomes and products of such research work within the various majors that CIDE offers.